Electronic Currents and Magnetic Fields in H2+ Induced by Coherent Resonant Bichromatic Circularly Polarized Laser Pulses: Effects of Orientation, Phase, and Helicity - Bandrauk, André D.; Chelkowski, Szczepan; Yuan, Kai-Jun (Frontiers in Physics, 2021)
We theoretically study pulse phase and helicity effects on ultrafast magnetic field generation in intense bichromatic circularly polarized laser fields. Simulations are performed on the aligned molecular ion H_2^+ from numerical solutions of corresponding time dependent Schrödinger equations. We demonstrate how electron coherent resonant excitation influences the phase and helicity of the optically induced magnetic field generation. The dependence of the generated magnetic field on the pulse phase arises from the interference effect between multiple ionization pathways, and is shown to be sensitive to the molecular alignment and the laser polarization. Molecular resonant excitation induces coherent ring electron currents, giving enhancement or suppression of the phase dependence. Pulse helicity effects control laser induced electron dynamics in bichromatic circular polarization excitation. These phenomena are demonstrated by a molecular attosecond photoionization model and coherent electron current theory. The results offer a guiding principle for generating ultrafast magnetic fields and for studying coherent electron dynamics in complex molecular systems.